The Corrupt Commandant: The Criminal Biography of Commandant Barnie van der Merwe - Coetzee, Emile (Scientia Militaria - South African Journal of Military Studies, 2023)
Commandant Barnie van der Merwe was a career soldier who served in the South African Defence Force (SADF) from 1934. By 1957 he had become embroiled in tender fraud and bribery in the procurement of arms and supplies for military vehicles and equipment for the SADF. His career came to an end in September 1963 when he was arrested and found guilty of corruption. His case contributed to the proclamation of the 1964 Cillié Commission of Inquiry into alleged irregularities in arms procurement in the SADF and the Department of Defence (DOD). The commission’s report showcased the intrigue in which corrupt SADF and DOD officials such as Van der Merwe played a part for the sake of self-enrichment. This study sheds light on the criminal biography of Barnie van der Merwe by indicating precisely how and against whom he committed his crimes and arguing the historical significance of his criminal career.